To Believe in Historical Progress: On Axel Honneth’s Normative Grounding of Critique - Min Seong Kim (Fakultas Filsafat, Universitas Gadjah Mada Yogyakarta, 2022)
One of the most ambitious contributions Axel Honneth has made to critical theory consists in his attempt to ground the normativity of critique beyond communicative reason—the normative ground of critique that had been proposed by Honneth’s predecessor at the Institut für Sozialforschung, Jürgen Habermas. Defending an affirmative stance toward historical progress is critical to Honneth’s project, which attempts to pursue the aspiration of the Frankfurt School to practice a robust form of immanent critique: for preserving the idea of progress allows Honneth to derive the validity of the underlying normative presuppositions of the existing social order, thereby securing the normative grounds of critique without relying on transcendent or transhistorical principles. Through a consideration of an aspect of the relation between universality and particularity that remains undertheorized in Honneth’s account, this essay attempts to question the success of his strategy for grounding the normativity of critique.